Characterization of Biocomposite Film Coating for Food Paper Packaging - Fatin Alia Mustapha, Nurul; Iranati Md. Sharif, Zatul; Jai, Junaidah; Mohd Yusof, Noorsuhana; Adeib Idris, Sitinoor (International Journal of Engineering and Technology, 2018)
Paper and paperboard are commonly laminated with petroleum-based plastic such as polyethylene (PE) to enhance its barrier and mechanical properties. However, it cannot be degraded naturally by the environment. In an effort to counter this issue, natural sources biopolymer film was developed from cassava starch and carboxymethylcellulose (CMC) as alternatives in replacing PE. Different formulation viscosity was prepared by varying the contents of CMC in cassava starch from 0% to 50%. Characterizations analysis showed that sample BF 3 containing 10% w/w starch of CMC had the highest tensile strength (15 MPa), exhibited hydrophobic properties with contact angle higher than 90° and had the lowest moisture content. Fourier Transform Infrared (FTIR) analysis on BF 3 confirmed the presence of C-OH bending at C-6 of glycosidic ring indicated the presence of intermolecular and intramolecular hydrogen bond formation. A comparison study of BF 3 with commercially coating material  used in food packaging showed that BF 3 exhibit similar hydrophobic properties but higher tensile strength than the PE coating. Besides, thermogravimetric analysis identified that BF 3 had less residue and this indicated that BF 3 film degraded faster than the commercial. Thus, it can be stated that the develop biofilm could replace the currently used petroleum based derivative plastic in the food industry.
Keywords: Biocomposite film; Cassava starch; Carboxymethylcellulose; Food packaging; Paper coating